Pemanfaatan Teknologi Adsorbsi Sebagai Solusi Penyediaan Air Bersih Di Kabupaten Tanjung Jabung Barat Provinsi Jambi - Edwin Permana; Wahyudi Zahar; Aditya Deni Prabawa; Dicky Ardianto; Yuli Efrianti (Pengelola Jurnal Politeknik Negeri Ketapang, 2021)
Jambi Province is a province that has the 3rd largest peatland area in the island of Sumatra. The area of ​​peat land in Jambi Province reaches 736,227.20 ha or about 14% of the area of ​​Jambi Province. The area of ​​peat in West Tanjung Jabung Regency is 154,598 ha. Water on peatlands is not a good water category because water on peatlands often contains seeds or certain substances, which are not clear, which can cause diseases that support human survival. Peat water is one of the groundwater that does not meet health requirements that is used by some people who live in tidal or coastal areas. Due to this condition, it does not support the community to get clean water which causes the community to use peat water. Adsorption technology is one of the solutions to provide clean water in the village. The adsorbent used is activated carbon from cassava peels. It is hoped that this technology can help the surrounding community to help with the problem of lack of clean water